Hemodynamic and Metabolic Assessment of Neonates With Punctate White Matter Lesions Using Phase-Contrast MRI and T2-Relaxation-Under-Spin-Tagging (TRUST) MRI - Qi, Ying; Liu, Peiying; Lin, Zixuan; Lu, Hanzhang; Wang, Xiaoming (Frontiers in Physiology, 2018)
The brain’s hemodynamic and metabolism of punctate white matter lesions (PWML) is poorly understood due to a scarcity of non-invasive imaging techniques. The aim of this study was to apply new MRI techniques to quantify cerebral metabolic rate of oxygen (CMRO2), global cerebral blood flow (CBF), oxygen saturation fractions in venous blood (Yv) and oxygen extraction fraction (OEF) in neonates with PWML, for better understanding of the pathophysiology of PWML. Fifty-one newborns were recruited continuously, including 23 neonatal patients with PWML and 28 normal control neonates. Phase-contrast (PC) MRI and T2-Relaxation-Under-Spin-Tagging (TRUST) MRI were performed for the measurement of CBF and Yv. OEF and CMRO2 were calculated from the CBF and Yv values. The total maturation score (TMS) was assessed for each neonate on standard T1, 2-weighted images to evaluate cerebral maturation. The CMRO2, CBF, Yv and OEF values were compared between groups, and their associations with age and TMS were evaluated. Significant differences between PWML group and control group were found in CMRO2 (P=0.020), CBF (P=0.027), Yv (P=0.012), OEF (P=0.018). After age/maturation is accounted for, Yv and OEF showed significant dependence on the groups (P <0.05). Newborns with PWML had lower OEF and higher Yv. CMRO2, CBF and brain volume were correlated with age (P<0.001) and TMS (P<0.05). It is feasible to use non-invasive MRI methods to measure cerebral oxygen supply and consumptions in neonates with PWML. Newborns with PWML have lower oxygen consumption. Yv and OEF may be helpful for the diagnosis of PWML. The positive correlation between CBF and TMS, and between CMRO2 and TMS suggested that as myelination progresses, the blood supply and oxygen metabolism in the brain increase to meet the escalating energy demand.